(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2019)
This paper intends to elaborate a theoretical analysis of the concepts of perception and problem solving. Behavioral-analytic studies in these areas, despite the advances in empirical research, lack the elaboration of a more satisfactory conceptual framework. Experiments on repertoire recombination and Skinner’s interpretative analysis are examined. Interpretations are proposed about how the various interactions between operants and respondents can explain the perceptual phenomena and how they integrate the problem-solving chains. Through the examination of cases such as ambiguous figures, whose perception has significant similarities with insight, ways to include perceptual responses in studies on repertoire recombination are explored. Thus, it is expected to contribute to the elaboration of a more refined and integrated understanding of the phenomena in question, which may be useful, among other things, for the construction of future experimental designs.